Mr. Blackwell arriving at gala event - Unidentified photographer (Colorado State University. Libraries, 1996)
Photograph of Linda Carlson and Mr. Blackwell arriving at a gala event. Antigone Kotsiopulos is standing in the foreground, facing Carlson and Blackwell. In the background, is a white limousine.
Keywords: Fashion -- History; Fashion -- Exhibitions